Pharmacy and pain management in front of oncological patients - Silva, Alexandra Siqueira da; Braga, Rayene Pereira Leles; Queiroz, Fellipe José Gomes (Revista Coleta Científica, 2021)
Theme: self-medication in times of pandemic. Problem: What are the challenges for pharmacists facing self-medication during the new coronavirus pandemic by the Brazilian population? Hypothesis: the indiscriminate use of medications is a serious problem in times of pandemic, which threatens the physical and mental health of people who use these procedures. Objectives: to analyze the challenges faced by pharmacists in self-medication during the new coronavirus pandemic in the Brazilian population. Justification: in Brazil, self-medication represents a risk that can cause serious health problems and the pharmacist plays an important role in education regarding the use of medication. Methodology: This is a literature review. Results: during the pandemic, irrational drug use prevailed due to the supposed cure possibilities for Covid-19.